Os determinantes da abertura comercial: uma análise para a América Latina e o Caribe no período 2000-2020 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The objective of this study is to estimate the determinants of trade openness in the countries of Latin America and the Caribbean from 2000 to 2020, using a panel data methodology. To achieve this, an innovative trade openness index was employed, the Composite Trade Share by Squalli and Wilson (2011). The main findings revealed that resources provided by banks to the private sector, GDP per capita, the growth rate of the urban population, government expenditures on final consumption, gross fixed capital formation, and participation in economic blocs were the key determinants of trade openness in the region. For instance, a 10% increase in resources allocated to the private sector results in an approximate 2.3% growth in trade openness levels in Latin American and Caribbean countries. Similarly, a 10% increase in GDP per capita raises trade openness levels by about 4.2%, with statistical significance at the 10% level.
Keywords: determinantes; abertura comercial; américa latina e caribe; dados em painel; determinants; trade openness; latin america and the caribbean; panel data; Economia